Effects of Different Lengths of a Nucleic Acid Binding Region and Bound Nucleic Acids on the Phase Behavior and Purification Process of HBcAg Virus-Like Particles - Valentic, Angela; Müller, Jakob; Hubbuch, Jürgen (Frontiers in Bioengineering and Biotechnology, 2022)
Virus-like particles (VLPs) are macromolecular structures with great potential as vehicles for the targeted administration of functional molecules. Loaded with nucleic acids, VLPs are a promising approach for nanocarriers needed for gene therapy. There is broad knowledge for the manufacturing of the truncated wild-type lacking a nucleic acid binding site, that is mainly being investigated for vaccine applications. Whereas, for their potential application as nanocarrier for gene therapy Hepatitis B core Antigen (HBcAg) VLPs with a nucleic acid binding site for efficient cargo-loading are being investigated. VLP structure, loading and phase behavior is of central importance to their therapeutic efficacy and thereby considerably affecting the production process. Therefore, HBcAg VLPs with different lengths of the nucleic acid binding site were produced in E. coli. VLP attributes such as size, zeta potential and loading with host cell-derived nucleic acids were evaluated. Capsid’s size and zeta potential of the VLP constructs did not differ remarkably, whereas the analysis of the loading with host cell-derived nucleic acids revealed strong differences in the binding of host cell-derived nucleic acids dependent on the length of the binding site of the constructs, with a non-linear correlation but a two-zone behavior. Moreover, the phase behavior and purification process of the HBcAg VLPs as a function of the liquid phase conditions and the presence of host cell-derived nucleic acids were investigated. Selective VLP precipitation using ammonium sulfate was scarcely affected by the encapsulated nucleic acids. However, the disassembly reaction, which is crucial for structure homogeneity, separation of encapsulated impurities and effective loading of the VLPs with therapeutic nucleic acids, was affected both by the studied liquid phase conditions, varying pH and concentration of reducing agents, and the different VLP constructs and amount of bound nucleic acids, respectively. Thereby, effects of the presence of bound nucleic acids on the capsid stability were observed, following the two-zone behavior of the construct’s loading, and a resulting correlation between this capsid stability and the disassembly reaction could be derived.